Quantitative and qualitative assessment of timber harvesting residues: a case study of a balsa plantation in Papua New Guinea. Issue 1 (2nd January 2016) - Ghaffariyan, Mohammad Reza; Jenkin, Braden; Mitchell, Rick; Brown, Mark
Abstract: The quantity and quality of the harvesting residues in a balsa plantation in East New Britain Province of Papua New Guinea are reported in this paper. The plantation was harvested manually with a chainsaw and manpower to extract the industrial wood at age 6 years. A modified standard harvesting residue assessment method using plots on line transects was applied. The total weight of the harvest residues remaining on the site after wood extraction was 211.7 tGREEN ha − 1 (tonnes (green) per hectare). The major component was un-merchantable stem wood (121.3 tGREEN ha − 1 ; 57.3%), followed by bark (59.3 tGREEN ha − 1 ; 28.0%). This level of harvest residue was relatively greater than that reported in other studies, reflecting the combination of the log specification applied and the nature of the stem defects in balsa trees. The level of residues indicates the possibility of additional woody material recovery for bioenergy after consideration of sustainability issues. The average moisture content of the wood components of the residues was determined over two days. The average moisture content on the first day after harvesting was 50%, falling in the following day to about 48%. The abundance of five elements in the harvest residues was estimated using data from a single sample tree; of the elements assessed potassium was the most abundant while calcium was the least.